Fungicidal value of wood tar from pyrolysis of treated wood - Mazela, Bartłomiej (Waste management (New York, N.Y.), 2007)
The objective of the paper was to estimate the fungicidal value of wood tar extracted as a product of pyrolysis of wood previously treated with either creosote oil or CCB-type salt preservative. The effectiveness of wood treated with one of these two wood tar residuals was compared to the effectiveness of wood treated with virgin creosote oil (type WEI-B) and an untreated control. Wood was impregnated with alcohol solutions of the two extracted preservatives or virgin creosote oil and then subjected to the Coniophora puteana, Poria placenta and Coriolus versicolor fungi. The fungicidal values of the investigated preservatives were determined with the use of the short agar-block method and the aging test according to the standard EN 84. It was found that wood tar extracted by pyrolysis of old creosote-treated wood and then used to treat wood may have potential as a preservative for wood protection or as a component of preservatives